STUDY OF WATER CONTACT ANGLE ON SANDPAPER ROUGH SURFACE - Wuryanti, Sitri
An understanding of the interaction between multiphase fluid and solid is increasingly needed as the application of these concepts increases in many fields, including the industrial process such as oil drilling, lubrication, liquid coating, printing, spray quenching, and so on. This multiphase interaction is controlled by the properties of the surfaces that are in contact with each other, which can be determined by measuring the contact angle. This study aimed to observe the effect of surface roughness on the water contact angle of sandpaper with 4 different grit numbers, namely 60, 120, 180, and 240. In addition, changes in contact angle, maximum height, and the contact diameter of water droplets with time were also studied. The contact angle measurement was carried out using the sessile drop method with a set of experimental tools called the CAAI 2320 Contact Angle. The droplet image was recorded every 30 seconds and then processed using MyDropMeter software to measure the contact angle, maximum height, and contact diameter of the droplet. The surface roughness of the sandpaper was characterized based on 4 parameters, namely the cross-sectional area of the abrasive particles of the sandpaper (A), the surface wavelength (?), the surface wave-front height (h), and the Wenzel surface roughness factor (r). The results of this study indicated that the higher the surface roughness of the sandpaper, the lower the value of the contact angle and the maximum drop height measured. On the other hand, the droplet contact diameter looked increases as the surface roughness of the sandpaper increases. Wenzel's modeling represents the wetting state of water on the sandpaper surface which was indicated by the homogeneity of Young's contact angle values with the difference between the highest and lowest contact angles being only about 5°. The value of the contact angle, maximum height, and contact diameter of the droplet changes with time. The contact angle and maximum drop height decrease linearly with almost the same speed order of 10-4, while the droplet contact diameter decrease quadratically with a speed order of 10-8 to 10-7.